The Effect of Welding Current Variations on the Tensile Strength of A36 Steel Plates in Shielded Metal Arc Welding (SMAW) - Mukhnizar Mukhnizar; Irfan Putra; Afdal Afdal (The Future of Education Journal, 2026)
During the welding process, the metal will experience a thermal cycle, which is a rapid heating and cooling process in the welding area that causes a metallurgical process, the deformation that occurs will affect the results of the welding such as the type of defects produced, joint strength, tensile strength and metal microstructure (Teguh Wiyono, 2012). This study aims to determine the effect of welding current variations on the tensile strength of A36 carbon steel welds with the SMAW welding technique. From the results of the data processing obtained, it can be concluded that the highest tensile strength is found in the SMAW connection of ASTM A36 steel plates using a current of 140 A with a value of 448.3 Kgf/mm2. The lowest tensile strength is found in the SMAW connection of ASTM A36 steel plates using a current of 100 A with a value of 63.18 Kgf/mm2. And from testing 6 specimens using three (3) different types of current strength, it can be concluded that the greater the current strength value will produce a high tensile test value.